The Effect of Liberica Coffee on Liver Physiology and Histological Appearance of White Mice - Cindra Ayuning Kirana; Syamsurizal Syamsurizal; Diah Tri Utami (Indonesian Society for Cancer Chemoprevention, 2018)
Indonesia is one of the world's top coffee producing and exporting countries. Liberica coffee was one of the most widely cultivated types of coffee in Indonesia, especially in Tanjung Jabung Barat Jambi Province. Liberica coffee known as the coffee with highest levels of caffeine if compared with Arabica and Robusta coffee but the research about Liberica coffee was still very little if compared to the other two types of coffee. In the previous research, caffeine shown to be increasing alanine aminotransferase enzyme. Otherwise, coffee also contain chlorogenic acid which is a potent antioxidant and play a role in the protection of liver. The aim of this study are to investigate the effect of dark roasted Liberica coffee consumption on liver histological appearance, macroscopic anatomy and physiological function (serum glutamic-pyruvic transaminase (SGPT) level). This was an experimental study with posttest only control group design, using 45 male white mice and divided into 4 groups: control (with no coffee treatment), P1, P2 and P3 which were given coffee treatment consecutively 8000 ppm; 10.000 ppm and 12.000 ppm for 28 days. The result showed that liver histological damage level associated with the extent coffee intake. Although, the damage shown is still in a low level and has no impact in increasing SGPT level.Keywords : Liberica coffee, Liver, Histological appearance, SGPT level